2018
DOI: 10.1037/prj0000195
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of work for young adults diagnosed with serious mental health conditions.

Abstract: Our findings provide pertinent information for vocational rehabilitation services, recovery programs, and even parents on the importance of connecting young adults to jobs that enhance self-esteem and self-efficacy and are in line with their personal interests. Future research is needed to understand potential cultural and age differences in the meaning of work. (PsycINFO Database Record (c) 2018 APA, all rights reserved).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 52 publications
0
21
0
1
Order By: Relevance
“…A newer study has confirmed that for emerging adults with a diagnosed mental disorder, work is a resource. It gives them the possibility of becoming financially independent, and they experience an increase in their self-esteem and self-efficacy (Torres Stone et al, 2016). Early sensitization or early intervention services for mental disorders are generally recommended (Chan et al, 2015); however, such psychotherapeutic services focus less on self-esteem and self-efficacy and more on health competencies (knowledge in the field of mental health, help-seeking behavior, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A newer study has confirmed that for emerging adults with a diagnosed mental disorder, work is a resource. It gives them the possibility of becoming financially independent, and they experience an increase in their self-esteem and self-efficacy (Torres Stone et al, 2016). Early sensitization or early intervention services for mental disorders are generally recommended (Chan et al, 2015); however, such psychotherapeutic services focus less on self-esteem and self-efficacy and more on health competencies (knowledge in the field of mental health, help-seeking behavior, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Working is a source of financial reward and an additional income to the already existing one (Auerbach and Richardson, 2005; Saavedra et al , 2016), making people with severe mental illness feel financially independent (Torres Stone et al , 2018; Dunn et al , 2008) and providing them a sense of stability (Torres Stone et al , 2018). Also, by working, people with severe mental illness have the opportunity to improve the quality of their life by investing in education and cognitive improvement and by upgrading their mental health treatment (Eklund, 2009; Saavedra et al , 2016; Borg and Kristiansen, 2008; Dunn et al , 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies about the effectiveness of innovative group psychosocial rehabilitative interventions focused on sport activities and counseling [ 60 ], sport activity, mindfulness, psychoeducation [ 61 ] and job training [ 62 ], even when did not directly considered self-efficacy as an outcome nor mediator on outcomes, seem to provide the opportunity to enhance self-efficacy, self-esteem, self-confidence, and a positive self-image in people with severe psychosocial disabilities [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…People with psychosocial disabilities usually report poor quality of life (QoL) [ 1 , 2 ] and difficulties in social functioning [ 3 , 4 ]. QoL refers to the perceived overall wellbeing, including physical, psychological and social functioning [ 5 ].…”
Section: Introductionmentioning
confidence: 99%